Sosialisasi Sanitasi Total Berbasis Masyarakat Di Desa Sukasari Dan Panunggulan Kecamatan Tunjung Teja Kabupaten Serang - Euis Ismayati Yuniar; A. Machron Chairulfalah; Nurjaman; Trikawati; Lia Nurliana; Dwi Agung Riyanto (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Community-Based Total Sanitation (STBM) is very important and must be practiced, realized or actualized in the daily life of all community members. This is due to behavioral factors that contribute 30-35% to health status, so various ways are needed to make unhealthy behavior healthy, one of which is through the Community-Based Total Sanitation (STBM) program. The low level of clean and healthy living behavior in the school environment is partly due to the low level of public awareness in implementing clean and healthy living behaviors, such as open defecation so that our country's ODF (open defecation free/stop open defecation) rate is the 2nd lowest after India. , also community members never wash their hands with soap when they are going to eat, prepare unhealthy food and drink, throw trash in the wrong place, let alone take the initiative to build a garbage bank, and allow water to stagnate inside and in the yard. Socialization of clean and healthy living behavior is only implemented in the form of an appeal for behavior change so that people's lives are healthier and the Healthy District/City Program will be implemented. Moreover, Serang Regency, Pandeglang Regency and Lebak Regency are still lagging behind in Banten in the Healthy District/City Program. The three regencies have never received a basic-level Healthy District/City Award (Papada Award) because the ODF level is very low (below 7%). Thus, information is urgently needed regarding the importance of clean and healthy living behavior and realizing STBM at the village level.